Service Quality at the Lebanese University: Faculty of Public Health (Journal of Universal Excellence, 2026)
Research Question (RQ): With the tremendous changes in the flow of global knowledge, higher education institutions are facing the questioning of its quality from the perspective of its primary customers, the students. The research question asks whether there are differences in service quality regarding expectations and perception and which dimensions need improvement. Service quality is one of the main perspectives that need to be integrated into the total quality strategies in higher education institutions for evidence of excellence and accreditation purposes.Purpose: This research aims to evaluate service quality at the faculty level, to keep up with the changing needs of students and integrate the needs and expectations into the quality improvement strategies at the higher education level. This study will attempt to set the path and identify factors for improvements and their prioritization.Method: SERVQUAL instrument was used for the GAPS model assessment of quality services and Improvement-Performance Analysis for prioritizing attributes as strategic goals for improvement. The data were collected at the Lebanese University (LU) at the Faculty of Public Health branch IV.Results: Quality service dimensions that have the most need for improvement are the dimensions of Empathy and Tangibles. Whereas, the specific attributes that indicated the need of improved Performance and high Importance were: hearing and understanding students’ specific needs, providing suitable timing of services, using up-to-date equipment and technology, showing honest interest in solving a student’s problem, and providing services as promised.Organization: Lebanese University will have the improvement strategies that are needed in its improvement plan for accreditation. At the faculty level, it can set a standard of operation based upon the results and reassess the evaluation for evidence of effective changes when completed.Society: Quality service from the perspective of students will sustain the competency and assurance of the public higher education institutions in comparison to private ones. Public university’s well being is the supportive pillar for the education of all students from different social status.Originality: This study will be the first to assess service quality at LU. It is hoped to be the trigger for further similar and continuous series of assessments for all faculties that can gather a precise view of the needed improvements and set them as strategies in LU strategic plans.Limitations / further research: Service quality is dynamic. It changes with changing generations and with differing backgrounds. Continuous measurement and use of the scale will provide a better, more accurate view of the situation.
Keywords: Service Quality; Higher Education; SERVQUAL; Gap Analysis; Importance-Performance Analysis; Lebanese University Faculty of Public Health Branch IV